Association Between Long-Term Aspirin Use and Frailty in Men: The Physicians' Health Study. (11th September 2020) - Orkaby, Ariela R; Yang, Laiji; Dufour, Alyssa B; Travison, Thomas G; Sesso, Howard D; Driver, Jane A; Djousse, Luc; Gaziano, J Michael
Abstract: Background: Chronic inflammation may lead to frailty, however the potential for anti-inflammatory medications such as aspirin to prevent frailty is unknown. We sought to examine the association between long-term aspirin use and prevalent frailty. Methods: We included 12 101 men ≥60 years who participated in the Physicians' Health Study I, a completed aspirin randomized controlled trial (1982–1989). Annual questionnaires collected self-reported data on daily aspirin use, lifestyle, and clinical variables. Average aspirin use was summed into 2 categories: ≤60 days/year and >60 days/year. Frailty was assessed using a 33-item index 11 years after trial completion. A score of ≥0.21 was considered frail. Propensity score inverse probability of treatment weighting was used for statistical control of confounding. Logistic regression models estimated odds of frailty as a function of categories of average aspirin use. Results: Mean age was 70.5 years (range 60–101). Following an average of 11 ± 0.6 years of follow-up, aspirin use was reported as ≤60 days/year for 15%; 2413 participants (20%) were frail. Frequency of aspirin use was associated with smoking, alcohol consumption, hypertension, and cardiovascular disease, but negatively associated with bleeding and Coumadin use. The odds ratio (95% confidence intervals) for frailty was 0.85 (0.76–0.96) for average aspirin use >60 days/year versus aspirin use ≤60 days/year. Results were similar using an alternate definition of frailty. Conclusions: Long-term regular aspirin use is inversely associated with frailty among older men, even after consideration of multimorbidity and health behaviors. Work is needed to understand the role of medications with anti-inflammatory properties on aging.